The Impact of Young Entrepreneurs’ Network Entrepreneurship Education and Management System Innovation on Students’ Entrepreneurial Psychology - Wang, Zeyu; Tang, Run; Cheng, Xin (Frontiers in Psychology, 2021)
The purpose of the study is to solve the problems existing in entrepreneurship education and management under computer technology. The teaching content of entrepreneurship education in colleges and universities is proposed. Since entrepreneurship education is practical, the auxiliary mechanism of entrepreneurship education also needs to be highly integrated with entrepreneurship practice. First, the network entrepreneurship teaching and management system is constructed, and students' entrepreneurial creativity, communication ability, leadership ability, and qualities are taken as the research object. Second, the traditional teaching method, case study method, and scene simulation method are used to analyze and discuss the influence of the entrepreneurial teaching mode, entrepreneurial experience, and entrepreneurial ability on students' entrepreneurial psychology. Finally, the questionnaire survey is used to conduct the relative sample t-test (Student's t-test), and the influence of three teaching methods on students’ learning effects is analyzed. The influence of the three teaching methods on students’ entrepreneurial psychological states is further analyzed by the statistical method. The experimental results show that the test result of the scene simulation method and the traditional teaching method is 0.584, the test result of the scene simulation method and the case study method is 0.842, and the test result of the case study method and the traditional teaching method is 0.595. This shows that the scene simulation method has a significant impact on students' entrepreneurial psychology and their entrepreneurial ability. In addition, students' cognition of professional status significantly affects their entrepreneurial psychology and attitudes, and the correlation coefficient is 0.576. Therefore, it is suggested that colleges and universities should adopt the scene simulation method to improve the teaching quality of entrepreneurship education and strengthen students' cognition of professional status and their entrepreneurial practice.